A case of foreign body in the subglottic region - Kamath, M. Panduranga (Springer India, 1999)
An impacted foreign body in the subglottis is a rare cause of upper airway obstruction in children. More often than not the diagnosis is delayed; especially where proper history is not forthcoming. This peculiar condition can masquade as laryngotracheobronchitis or a croup. Though it is rare, a foreign body in the subglottis should be kept in mind in the investigation of a child with stridor.